Lighter-load exercise produces greater acute- and prolonged-fatigue in exercised and non-exercised limbs - Farrow, J.; Steele, J.; Behm, D. G.; Skivington, M.; Fisher, J. P. (Research Quarterly for Exercise and Sport, 2021)
Purpose: The present study compared the fatigue and perceptual responses to volume-load matched heavier- and lighter- load resistance exercise to momentary failure in both a local/exercised, and non-local/non-exercised limb. Methods: Eleven resistance-trained men undertook unilateral maximal voluntary contraction (MVC) testing for knee extension prior to and immediately, 24 hr- and 48 hr- post heavier (80% MVC) and lighter (40% MVC) load dynamic unilateral knee extension exercise. Only the dominant leg of each participant was exercised to momentary failure using heavier and lighter loads, and perceptions of discomfort were measured immediately upon exercise cessation. Results: Point estimates and confidence intervals suggested that immediately post-exercise there was greater fatigue in both the exercised and non-exercised legs for the lighter- load condition. At 24 hr the exercised leg under the heavier-load condition had recovered to pre-exercise strength; however, the exercised leg under lighter- load condition had still not fully recovered by 48 hr. For the non-exercised leg, only the lighter-load condition induced fatigue; however, recovery had occurred by 48 hr. Median discomfort ratings were statistically significantly different (Z = -2.232, p = .026) between lighter and heavier loads (10 [IQR = 0] and 8 [IQR = 3], respectively). Conclusions: This study suggests that lighter-load resistance exercise induces greater fatigue in both the exercised- and non-exercised limbs, compared to heavier-load resistance exercise. These findings may have implications for exercise frequency as it may be possible to engage in heavier-load resistance exercise more frequently than a volume-load matched protocol using lighter loads.